The Socioeconomic Characteristics of Pig Farmers in the Tropics as a Determinant of Pig Production and Profitability - Dozie de A; Tamunotonye V (African Journal of Pig Farming, 2025)
In Nigeria's Imo State, the socioeconomic traits of pig farmers were examined as factors influencing their output and financial success. Determining the socioeconomic characteristics of pig farmers, identifying the pig production systems in the study area, estimating the costs and returns associated with pig production, analyzing the constraints to pig production in the study area, and describing the socioeconomic characteristics of pig farmers will be the specific objectives. For a detailed investigation, 90 pig farmers will be selected using a multi-stage random sample process. Structured questionnaires and secondary sources from conferences, seminars, journals, published and unpublished theses, and workshops provided the data for this study. The frequency distribution table and percentage response were used to record the first, second, and third objectives. Gross margin analysis and the Cobb Douglas production function, respectively, were used to address objectives iii and iv. The socioeconomic characteristics of the sampled farmers were as follows: they were male, older, educated, had a large household, were more likely to use family labor, were experienced, and the majority of pig farmers used intensive rearing techniques, while the least number used extensive methods. Additionally, the majority of farmers were involved in Farrow to finish enterprises, with animal breeding being the least common. The Cobb Douglas production function revealed that piglet type, raising experience, organization membership, and pharmaceutical costs were positively correlated with the profitability of pig farming. Because their return scale was 3.0141, which is higher than unitary, the pig farmers in the study area were working in stage 1 (irrational stage), which is not at their optimal production size. With net farm income of N334,542 and gross revenue of N740,000 per sampled farmer, pig production was profitable in the research area. High feed and housing costs, issues with product marketing, high labor costs, and limited financing availability were the main obstacles to pig production in the research area. Among the suggestions made were the necessity of improving farmers' access to commercial bank credit, encouraging extension agents by covering their local transportation costs while doing their tasks, and guaranteeing that farmers have access to legitimate medications.